Bangladesh’s transition from state to market: problem and prospect of globalisation - Quddus, S. M. Abdul (The University of Chittagong Press, 2000)
In response to new global economic order Bangladesh like other developing countries has taken a series of masures to disengage to herself from the state-controlled economy during the last two decades. The goverments ruling the country since independence have taken masures to sell off public corporations, delegated the provision of the most basic services to the private sector and deregulated its domestic economy. Not only the present government but also the regimes come to power particularly after 1975 have also jettisoned protectionist trade and investment policies by slashing import restrictions and creative incentives to attract foreign capital. In a nutshell, Bangladesh is trying to satisfy the growing demands of international trade and business. This paper examines the overall economic reform efforts and its impacts on Bangladesh's movement towards globalization.